LabVIEW A Flexible Environment for Modeling and Daily Laboratory Use - de Asmundis, Riccardo (IntechOpen, 2021)
The LabVIEW software environment from National Instruments is used by engineers and scientists worldwide for a variety of applications. This book examines many of these applications, including modeling, data acquisition, monitoring electrical networks, studying the structural response of buildings to earthquakes, and more.